TCR-like antibody drug conjugates mediate killing of tumor cells with low peptide/HLA targets. Issue 4 (19th May 2017) - Lowe, Devin B.; Bivens, Camille K.; Mobley, Alexis S.; Herrera, Christian E.; McCormick, Amanda L.; Wichner, Timea; Sabnani, Manoj K.; Wood, Laurence M.; Weidanz, Jon A.
ABSTRACT: The currently marketed antibody-drug conjugates (ADC) destabilize microtubule assembly in cancer cells and initiate apoptosis in patients. However, few tumor antigens (TA) are expressed at high densities on cancer lesions, potentially minimizing the therapeutic index of current ADC regimens. The peptide/human leukocyte antigen (HLA) complex can be specifically targeted by therapeutic antibodies (designated T cell receptor [TCR]-like antibodies) and adequately distinguish malignant cells, but has not been the focus of ADC development. We analyzed the killing potential of TCR-like ADCs when cross-linked to the DNA alkylating compound duocarmycin. Our data comprise proof-of-principle results that TCR-like ADCs mediate potent tumor cytotoxicity, particularly under common scenarios of low TA/HLA density, and support their continued development alongside agents that disrupt DNA replication. Additionally, TCR-like antibody ligand binding appears to play an important role in ADC functionality and should be addressed during therapy development to avoid binding patterns that negate ADC killing efficacy.